Outcomes of the National Heart, Lung, and Blood Institute K12 program in emergency care research: 7‐year follow‐up. (11th August 2022) - Morris, Cynthia D.; Cook, Jennifer N. B.; Lin, Amber; Scott, Jane D.; Kuppermann, Nathan; Callaway, Clifton W.; Yealy, Donald M.; Lowe, Robert A.; Richardson, Lynne D.; Kimmel, Stephen; Holmes, James F.; Collins, Sean; et al.
Abstract: Background: Long‐term follow‐up for clinician–scientist training programs is sparse. We describe the outcomes of clinician–scientist scholars in the National Heart Lung and Blood Institute (NHLBI) K12 program in emergency care research up to 8.7 years after matriculation in the program. Methods: This was a cohort study of faculty clinician–scientist scholars enrolled in a NHLBI K12 research training program at 6 sites across the US, with median follow‐up 7.7 years (range 5.7–8.7 years) from the date of matriculation. Scholars completed electronic surveys in 2017 and 2019, with the 2019 survey collecting information for their current work setting, percent time for research, and grant funding from all sources. We used NIH RePorter and online resources to verify federal grants through March 2021. The primary outcome was a funded career development award (CDA) or research project grant (RPG) where the scholar was principal investigator. We included funding from all federal sources and national foundations. Results: There were 43 scholars, including 16 (37%) women. Over the follow‐up period, 32 (74%) received an individual CDA or RPG, with a median of 36 months (range 9–83 months) after entering the program. Of the 43 scholars, 23 (54%) received a CDA and 22 (51%) received an RPG, 7 (16%) of which were R01s. Of the 23 scholars who received a CDA, 13 (56%) subsequently had an RPG funded. Time to CDA or RPG did not differ by sex (women vs. men log‐rank test p  = 0.27) or specialty training (emergency medicine versus other specialties, p  = 0.59). Conclusions: After 7 years of follow‐up for this NHLBI K12 emergency care research training program, three quarters of clinician–scientist scholars had obtained CDA or RPG funding, with no notable differences by sex or clinical training.